MODERN PARALLELS CAUSED BY READING THE STORY KOMATSU SAKE "PAPER OR HAIR" - IAKOVLEVA, E.L (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2021)
In the optics of attention was the story of the Japanese writer Komatsu Sake "Paper or hair", written in 1963. According to the content, the loss of paper changed the usual way of life of people, becoming a source of existential fears. As we believe, the artistic narrative anticipates the events of our time associated with the spread of the coronavirus infection COVID-19. An artistic description of the situation by a Japanese writer, a phenomenological immersion in reality and theoretical reflections by M. Heidegger's work on the existential of fear helped to reconstruct the psychological States of people in the context of a pandemic and to identify the structure of fear. In modern life, fear manifests itself in three aspects: before-than fear, fearfulness and about-than fear. As a result of the all-embracing nature of fear, the fearogenicity of being is born, which violates the stability of the individual's existence, its being in, dwelling in, and mastering with. The above leads to the individual's awareness of the direction of life towards death, which forces him to adapt to new conditions. As a support of the personality in its opposition to fear, we can call hope and effective manifestations that perform the role of care.